(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The study of vascular anatomy in plant species provides essential insights into their physiological adaptations, ecological roles, and potential applications in pharmacology and medicine. This study focuses on the comparative analysis of the vascular structures of Maerua oblongifolia, Marsdenia volubilis and Sansevieria roxburghiana. Maerua oblongifolia and Marsdenia volubilis two climber species known for their medicinal properties. Both species belong to distinct families, Capparaceae and Apocynaceae, respectively, but exhibit similar growth habits and environments, making them suitable for comparative vascular analysis. Sansevieria roxburghiana belongs to family Agavaceae. Histological examinations were conducted on the stems and roots of each species to observe the arrangement, size, and distribution of xylem and phloem tissues. Maerua oblongifolia was found to possess well-developed xylem vessels adapted for efficient water transport, a feature likely beneficial for survival in arid conditions. Conversely, Marsdenia volubilis exhibited a denser phloem network, which may support its climbing habit and facilitate nutrient distribution across its elongated structure. The study concludes that while these three species have unique vascular adaptations related to their growth forms and environmental demands, these structural characteristics also contribute to their medicinal applications. The vascular structures likely play a role in the synthesis and storage of bioactive compounds. Findings from this comparative analysis of Maerua oblongifolia, Marsdenia volubilis and Sansevieria roxburghiana used for electuary in consumptive complaints and chronic cough of long standing contribute to the broader understanding of plant vascular anatomy and its implications for botanical pharmacology, ecology, and sustainable medicinal plant use.